2020
DOI: 10.1101/2020.06.21.156273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial retrons function in anti-phage defense

Abstract: Retrons are bacterial genetic elements comprised of a reverse transcriptase (RT) and a non-coding RNA. The RT uses the non-coding RNA as a template, generating a chimeric RNA/DNA molecule in which the RNA and DNA components are covalently linked. Although retrons were discovered three decades ago, their function remained unknown. In this study we report that retrons function as anti-phage defense systems. The defensive unit is composed of three components: the RT, the non-coding RNA, and an effector protein. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 59 publications
3
66
0
3
Order By: Relevance
“…The first of these roles is thought to be mediated by the RT and msDNA, with the linked effector protein responsible for toxin/antitoxin functions. Furthermore, according to these reports ( 81 , 82 ), a large number of retrons, but not all are associated with defense genes in defense islands. It would be interesting to know whether there are specific retron systems consistently unrelated the known and novel candidate defense systems recently described ( 81 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first of these roles is thought to be mediated by the RT and msDNA, with the linked effector protein responsible for toxin/antitoxin functions. Furthermore, according to these reports ( 81 , 82 ), a large number of retrons, but not all are associated with defense genes in defense islands. It would be interesting to know whether there are specific retron systems consistently unrelated the known and novel candidate defense systems recently described ( 81 ).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it was reported that some retrons members of the type systems I-A (Retron+ATPase+HNH), II-A3 (Nuc_deoxy+Retron), I-C1 (Retron-Toprim) and XII (Retron-TIR) defined here mediate antiphage defense and that the additional proteins or RT-fused domains are also required for activity ( 81 ). Moreover, a recent report ( 82 ) and two pre-prints ( 83 , 84 ) have also suggested that retrons may be novel anti-phage defense systems and that they may function as a toxin/antitoxin system. The first of these roles is thought to be mediated by the RT and msDNA, with the linked effector protein responsible for toxin/antitoxin functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent booming of metagenomic analysis has suggested that a large number of uncharacterized defense systems exist in bacteria (9). As predicted, an increasing number of defense system were validated successively (10)(11)(12). Doron et al predicted and experimentally verified ten potential anti-phage defense systems, although their molecular mechanisms are not yet understood (10).…”
Section: Introductionmentioning
confidence: 97%
“…Retrons encode 12%-14% of the bacterial RTs and are the second frequent class of RTs [4,6]. Although retrons were discovered three decades ago, their function remained unknown until recently that they were found to function as phage defense mechanisms [11,12]. Bacterial retrons are non-LTR-retroelements that produce multicopy single-stranded DNAs (msDNAs).…”
Section: Introductionmentioning
confidence: 99%